Metabolic activation and toxicological evaluation of polychlorinated biphenyls in Drosophila melanogaster - Idda, T. (Sci Rep, 2020)
Degradation of polychlorinated biphenyls (PCBs) is initiated by cytochrome P450 (CYP) enzymes and includes PCB oxidation to OH-metabolites, which often display a higher toxicity than their parental compounds. In search of an animal model reflecting PCB metabolism and toxicity, we tested Drosophila melanogaster, a well-known model system for genetics and human disease. Feeding Drosophila with lower chlorinated (LC) PCB congeners 28, 52 or 101 resulted in the detection of a human-like pattern of respective OH-metabolites in fly lysates. Feeding flies high PCB 28 concentrations caused lethality. Thus we silenced selected CYPs via RNA interference and analyzed the effect on PCB 28-derived metabolite formation by assaying 3-OH-2′,4,4′-trichlorobiphenyl (3-OHCB 28) and 3′-OH-4′,4,6′-trichlorobiphenyl (3′-OHCB 28) in fly lysates. We identified several drosophila CYPs (dCYPs) whose knockdown reduced PCB 28-derived OH-metabolites and suppressed PCB 28 induced lethality including dCYP1A2. Following in vitro analysis using a liver-like CYP-cocktail, containing human orthologues of dCYP1A2, we confirm human CYP1A2 as a PCB 28 metabolizing enzyme. PCB 28-induced mortality in flies was accompanied by locomotor impairment, a common phenotype of neurodegenerative disorders. Along this line, we show PCB 28-initiated caspase activation in differentiated fly neurons. This suggested the loss of neurons through apoptosis. Our findings in flies are congruent with observation in human exposed to high PCB levels. In plasma samples of PCB exposed humans, levels of the neurofilament light chain increase after LC-PCB exposure, indicating neuronal damage. In summary our findings demonstrate parallels between Drosophila and the human systems with respect to CYP mediated metabolism and PCB mediated neurotoxicity.